Threat Assessment and Locomotion: Clinical Applications of an Integrated Model of Anxiety and Postural Control - Staab, Jeffrey P.; Balaban, Carey D.; Furman, Joseph M. (Seminars in Neurology, 2013)
Interactions between anxiety and vestibular symptoms have been described since the late 1800s. Typically, they have been conceptualized as bidirectional effects of one condition on the other (i.e., anxiety disorders as a cause of vestibular symptoms and vestibular disorders as a cause of anxiety symptoms). Over the past 30 years, however, a steady progression of neurophysiological investigations of gait and stance under conditions of postural threat, neuroanatomical studies of connections between threat assessment and vestibular pathways in the brain, and clinical research on anxiety-related vestibular conditions has offered the building blocks of a more integrated model. In this newer concept, threat assessment is an integral component of spatial perception, postural control, and locomotion in health and disease. It is not imposed on the vestibular system from the outside or simply reactive to vestibular dysfunction, but an inherently necessary part of every aspect of mobility. In this article, the authors review evidence that supports this model and then use it to examine common neurotologic conditions in which anxiety-related processes play important roles—fear of falling, primary and secondary anxiety disorders in patients with vestibular symptoms, and chronic subjective dizziness.
Keywords: trait anxiety; state anxiety; anxiety disorders; spatial orientation; posture